Spatial Effects of Foreign Direct Investment Flows on Industrial Performance in Sub-Saharan African Countries - (:unkn) unknown (My University, 2022)
This paper rigorously analyzes the effects of foreign direct investment inflows on the industrial performance in the Sub-Saharan African (SSA) economies. Applying the Durbin spatial method (SDM) on a two-sector model to account for spatial effects, the empirical results show that the higher the capacity of SSA countries to attract foreign investments, the higher is the job-inducing effect and value-added created in the industrial sector, while no technology transfer was induced. This finding highlights the importance for the countries of sub-Saharan Africa to direct foreign direct investment towards strategic sectors where they benefit from comparative advantages and improve the business climate to attract more FDI, a pledge of any industrial development.
Keywords: African Research